(untitled) (Annual of the Faculty of Philosophy in Skopje, 2009)
In the period between the two world wars, political and the security situation in Macedonia under the Serbian authorities was the main subject for interest of securities and intelligences services of the Kingdom of SCS (Yugoslavia). The secret documents and reports which were prepared in the Ministry for internal affairs of the Yugoslavian state pointed the Macedonian organization IMRO as the one of most important reasons of unstability in Vardar part of Macedonia. That’s why, the Serbian security authorities constantly were occupied with creating of state strategy for struggle against IMRO and other organizations in the Macedonian revolutionary movement. Across good prepared propaganda activities, the government of the Kingdom of SCS (Yugoslavia) succeeded to gain the public opinion and to justify the repressive measures in Macedonia under the Serbian authorities, with excuse that they are pointed against IMRO as an antiserbian and antigovernment organization.